Memes and consciousness: Friend or foe? - Tan, Kock Wah; Zaimuariffudin Shukri, Nordin (Elsevier Ltd., 2013)
Besides the renowned biologist, Richard Dawkins, Dennett is amongst the first to be cognizance of the importance of memes, making it central in the formulation of a Dennettian theory of consciousness. The importance of memes in Dennett's theory of consciousness lies second only to his heterophenomenological theory. This paper argues that Dennett's conception of meme and consciousness is flawed. It raises difficult and thorny issues that could not be easily resolved and hence discrediting Dennett's theorizing of consciousness generally.